İlköğretim 4. sınıf öğrencilerine “açılar” konusunun öğretilmesinde proje tabanlı öğretim yönteminin etkisinin icelenmesi - Akgül, Esra (My University, 2011)
ÖNSÖZ Vakıflar, Osmanlı toplumunun en önemli kurumlarından biridir. Bu kurumlarla ilgili günümüzde pek çok çalısma yapılmıs olsa da bu çalısmalar daha ziyade vakıfların tarihi yönüyle ilgili olup, vakıfların hukukî yönlerinin, tam anlamıyla çalısıldığını söylemek mümkün değildir. Bu çalısma, Osmanlı vakıf hukukunun anlasılmasına ufak da olsa bir katkıda bulunma amacıyla hazırlanmıstır. Bu çalısma pek çok kisinin katkısı ile ortaya çıkmıstır. Öncelikle çalısmam boyunca benden desteğini esirgemeyen ve her konuda bana yardımcı olan danısman hocam Prof. Dr. Vecdi Akyüz’e, yine bu süreçte yardımlarını gördüğüm Prof. Dr. Murteza Bedir’e ve bu çalısmayı değerli elestirileri ile gelistirmis olan Doç. Dr. Nuh Arslantas ile Yrd. Doç. Dr. Sami Erdem’e tesekkürlerimi sunarım. Ayrıca yüksek lisans dönemi boyunca çalısmamı eksiksiz bir sekilde yürütebilmem için bana her türlü desteği sağlayan Đlimler ve Sanatlar Merkezi (ĐSM) hocalarına, tez boyunca Süleymaniye Kütüphanesi’ndeki eserlere ulasabilmem hususunda her türlü kolaylığı gösteren kütüphane müdürü Emir Es’e, bu süreçte rahat bir çalısma ortamı sağlayan ĐSAM yetkililerine ve eğitim hayatım boyunca benden desteklerini esirgemeyen aileme tesekkür eder, bu çalısmanın bu alanda yapılacak çalısmalara bir katkısı olmasını temenni ederim.

The purpose of this study is to find out the effect of project based learning on Mathematical Education students in Angles unit in terms of comprehension, permanence of information learned and attitude towards mathematics course. The research was applied to 41 students of fourth grade in second semester of 2010 - 2011 educational year in Cemal Artüz primary school. The model of the study is pretest - posttest experimental method with experimental control groups. The students were separated into two groups. One of the groups is control group, whereas the other one is experimental group. Unit of angles was taught using project based learning method to experimental group, while the same unit is taught using presentation method to control group. In the beginning of the implementation, Angles Unit Success Test was applied as pretest, and Mathematics Course Attitude Test was applied as attitude pretest. At the end of the implementation, Angles Unit Success Test was applied as posttest and Mathematics Course Attitude Test was applied as attitude posttest. Four weeks after the end of implementation, Angles Unit Success Test was applied again in order to measure permanence of the outcomes. After eight weeks of implementation, all data gathered were analyzed using SPSS 16.00 (Statistical Package of The Social Sciences). Paired-Samples T Test were used for analyzing data in order to compare differances between pretest and posttest success scores and attitudes levels. Significance level was accepted as 0.05 when interpreting analysis results. As a result, the difference of posttest and permanence test between experimental and control group was found significant while there is no significant difference between pretest scores. It was determined that project based learning method applied on experimental group is more efficient than presentation method applied on control group in terms of student success and attitude towards mathematics course. The resuts were discussed in relation to relevant studies. Suggestions have been made according to the results of the study.
Keywords: İlköğretim_Öğrenim ve Öğretim; Öğrenim ve Öğretim; Proje Tabanlı Öğretim